Tennis bounces back in Kedah: Association active again after more than a decade. - Noh, Dasheer (The Star (Metro North), 2013)
MOHD Izaudin Hamdi scored a double in the Kedah closed tennis championships at the Universiti Utara Malaysia courts in Sintok.He won the open category singles and doubles titles. In the singles he defeated Mohd Shamil Mazlan 86 before joining forces with Akmal Hakim Salleh to win the doubles title too.